Methylated Cytokinins from the Phytopathogen Rhodococcus fascians Mimic Plant Hormone Activity . Issue 2 (6th August 2015) - Radhika, Venkatesan; Ueda, Nanae; Tsuboi, Yuuri; Kojima, Mikiko; Kikuchi, Jun; Kudo, Takuji; Sakakibara, Hitoshi
Abstract : Methylated cytokinins contribute to pathogenesis as hormone-mimics. Abstract: Cytokinins (CK s), a class of phytohormones that regulate plant growth and development, are also synthesized by some phytopathogens to disrupt the hormonal balance and to facilitate niche establishment in their hosts. Rhodococcus fascians harbors the fasciation ( fas ) locus, an operon encoding several genes homologous to CK biosynthesis and metabolism. This pathogen causes unique leafy gall symptoms reminiscent of CK overproduction; however, bacterial CK s have not been clearly correlated with the severe symptoms, and no virulence-associated unique CK s or analogs have been identified. Here, we report the identification of monomethylated N   6 -(∆ 2 -isopentenyl)adenine and dimethylated N   6 -(∆ 2 -isopentenyl)adenine (collectively, methylated cytokinins [MeCK s]) from R. fascians . MeCK s were recognized by a CK receptor and up-regulated type-A ARABIDOPSIS THALIANA RESPONSE REGULATOR genes. Treatment with MeCK s inhibited root growth, a hallmark of CK action, whereas the receptor mutant was insensitive. MeCK s were retained longer in planta than canonical CK s and were poor substrates for a CK oxidase/dehydrogenase, suggesting enhanced biological stability. MeCK s were synthesized by S -adenosyl methionine-dependent methyltransferases (MT1 and MT2) that are present upstream of the fas genes. The best substrate for methylation was isopentenyl diphosphate. MT1 and MT2 catalyzed distinct methylation reactions; only the MT2 product was used by FAS4 to synthesize monomethylated N   6 -(∆ 2 -isopentenyl)adenine. The MT1 product was dimethylated by MT2 and used as a substrate by FAS4 to produce dimethylated N   6 -(∆ 2 -isopentenyl)adenine. Chemically synthesized MeCK s were comparable in activity. Our results strongly suggest that MeCK s function as CK mimics and play a role in this plant-pathogen interaction.